Separation of Copper and Zinc from aqueous solution using Liquid-Membrane-Gel (LMG) containing Trioctylphosphine Oxide TOPO as Carrier - TAOUALIT , Nadjet; ABIDAT , İsmail; HADJ-BOUSSAAD, Djamal-eddine (International Journal of Computational and Experimental Science and Engineering, 2017)
Transfer and extraction of metallic species (Ag+ and Cu2+ ions) through a flat sheet dense supported-liquid-membrane was investigated previously [1, 2] using thin sheets of polybutadiene rubber cross-linked with 0.1% and/or 0.4% of dicumylperoxyde at 160°C for 15 minutes noted BR1 and for 5 minutes noted BR2 [3]. In this work, column filled with a liquid-membrane-gel LMG in form of beads impregnated beforehand with the solvating organo-phosphoric carrier the trioctyl phosphine oxide TOPO, was used to study the extraction-concentration-recovery and the transport of Cu (II) and Zn (II) from an aqueous solution. Extraction of Cu (II) at different pH aqueous solutions has been described. The speciation of the extracted complexes in the membrane supported organic phase (extractant) was also, performed using the theoretically derived equations to elucidate the stoichiometry and the Cu (II) mechanism complexation through the liquid-membrane-gel LMG. Kinetic parameters were calculated from the experimental data. About 86-97% and 50-82% of respectively copper and zinc, were extracted from aqueous solutions at pH = 6 according to first-order kinetics and the separation factor away from the unit. The solvated copper species by TOPO are of the type [Cu(NO3)2]TOPO.